I know that in some countries, the long division of polynoms is being written in a different way. I will use the one that is familiar for me though and hope that you can convert it into your notation easily. :-)
Let me explain to you how to do the long division - and if you already know, you can skip to the end of the answer to see the whole division there.
========================================
1) First, check that the the terms in your numerator and denominator are ordered by the power of x - this is already the case for you.
2) Now, take the first term - the one with the biggest power - from the numerator and divide it by the first term - the one with the biggest power - from the denominator.
In your case, it's 2x^3 -: x = 2x^2, so you get:
color(white)(xii)(color(red)(2x^3) - 3x^2 color(white)(x)+ 3x - 4) -: (color(red)(x)-2) = color(red)(2x^2)
3) As next, you need to backwards multiply your new result (2x^2) with the denominator, so compute 2x^2 * (x-2) = 2x^3 - 4x^2 and subtract it from your numerator:
color(white)(xii)(2x^3 - 3x^2 color(white)(x) + color(grey)(3x) - 4) -: (color(blue)(x-2)) = color(blue)(2x^2)
-(color(blue)(2x^3 - 4x^2))
color(white)(x)(color(white)(xxxxxxxx))/()
color(white)(xxxxxxx) x^2 + color(grey)(3x)
4) As expected, you don't have a x^3 term anymore, and your new term with the highest power of x in the numerator is x^2, so you need to divide x^2 by x:
color(white)(xii)(2x^3 - 3x^2 color(white)(x) + 3x - 4) -: (color(red)(x)-2) = 2x^2 + color(red)(x)
-(2x^3 - 4x^2)
color(white)(x)(color(white)(xxxxxxxx))/()
color(white)(xxxxxxx) color(red)(x^2) + 3x
5) Again, do the backward multiplication and subtract the result:
color(white)(xii)(2x^3 - 3x^2 color(white)(x) + 3x color(white)(x) color(grey)(- 4)) -: (color(blue)(x-2)) = 2x^2 + color(blue)(x)
-(2x^3 - 4x^2)
color(white)(x)(color(white)(xxxxxxxx))/()
color(white)(xxxxxxx) x^2 + 3x
color(white)(xxxiix) -(color(blue)(x^2 - 2x))
color(white)(xxxxxx)(color(white)(xxxxxx))/()
color(white)(xxxxxxxxxxx) 5x color(white)(x)color(grey)(- 4)
6) As next, divide 5x by x...
color(white)(xii)(2x^3 - 3x^2 color(white)(x) + 3x color(white)(x) - 4) -: (color(red)(x)-2) = 2x^2 + x + color(red)(5)
-(2x^3 - 4x^2)
color(white)(x)(color(white)(xxxxxxxx))/()
color(white)(xxxxxxx) x^2 + 3x
color(white)(xxxiix) -(x^2 - 2x)
color(white)(xxxxxx)(color(white)(xxxxxx))/()
color(white)(xxxxxxxxxxx) color(red)(5x) color(white)(x)- 4
7)... and perform the backward multiplication and subtraction...
color(white)(xii)(2x^3 - 3x^2 color(white)(x) + 3x color(white)(x) - 4) -: (color(blue)(x-2)) = 2x^2 + x + color(blue)(5)
-(2x^3 - 4x^2)
color(white)(x)(color(white)(xxxxxxxx))/()
color(white)(xxxxxxx) x^2 + 3x
color(white)(xxxiix) -(x^2 - 2x)
color(white)(xxxxxx)(color(white)(xxxxxx))/()
color(white)(xxxxxxxxxxx) 5x color(white)(x)- 4
color(white)(xxxxxxxxi) -(color(blue)(5x color(white)(x)- 10))
color(white)(xxxxxxxxxxx)(color(white)(xxxxxxx))/()
color(white)(xxxxxxxxxxxxxxxxi) 6
8) At this point, as you can't divide 6 -: x anymore, you have finished your division and have the remainder 6 at the end:
========================================
Solution:
(2x^3 - 3x^2+3x-4)/(x-2) = 2x^2 + x + 5 + (6)/(x-2)